Mengoptimalkan Plasticitas Otak dalam Pembelajaran Bahasa Arab : Pendekatan Neurolinguistik untuk Mahasiswa - Aifanisa Rahman (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research examines the optimization of brain plasticity in Arabic language learning through a neurolinguistic approach, using a literature review method. Brain plasticity, the brain's ability to adapt and change through learning and experiences, plays a crucial role in language acquisition. Neurolinguistic approaches, which integrate techniques such as task-based learning and the use of educational technology, have proven effective in enhancing language learning outcomes. Literature analysis indicates that learning techniques involving various sensory modalities and educational technology can stimulate new neural pathways, strengthening language comprehension and memory. Studies focused on Arabic language learning highlight that traditional approaches are less effective compared to more interactive and communicative methods. The use of technology such as mobile applications and augmented reality provides a dynamic and engaging learning experience for students. Practical recommendations include developing more interactive curricula, utilizing educational technology, and training educators in neurolinguistic techniques. This research emphasizes the importance of a multidisciplinary approach to enhance the effectiveness of Arabic language learning, providing insights and strategies to optimize language learning through a better understanding of brain plasticity and neurolinguistics.